COVID-19 vaccine reluctance and possible driving factors: A comparative assessment among pregnant and non-pregnant women - Rehman, Erum; Rehman, Nadia; Akhlaq, Muhammad; Hussain, Iftikhar; Holy, Ondrej (Frontiers in Public Health, 2023)
The coronavirus disease of 2019 (COVID-19) constitutes a serious threat to pregnant women. One of the key strategies for preventing and managing the COVID-19 epidemic is vaccination. Herd immunity is significantly hampered by COVID-19 vaccine reluctance, which poses a potential threat to population health. Therefore, the present work intends to ascertain the incidence and severity of COVID-19 vaccine hesitancy among Pakistani pregnant women, the determinants driving their decision, and a comparative assessment with non-pregnant participants. This cross-sectional survey was carried out from November 2021 to February 2022. The validated vaccination attitude examination (VAX) scale about vaccination reluctance was undertaken by participants, who were also required to indicate whether they would be inclined to acquire the COVID-19 vaccine along with the reasons for reluctance. In comparison to the non-pregnant category with 353 participants, the group of 372 pregnant participants who responded to the questionnaire had a much greater proportion of hesitant respondents. Likewise, contrasted to 31% of non-pregnant participants, about 40% of them attributed their willingness to get vaccinated against coronavirus to social media. They also demonstrated a considerably stronger mean score on all subcategories of the VAX measure. The adjusted odd ratio findings showed that the independent factors for vaccine reluctance appeared to be trusting rumors on social media (adj OR:2.58), not being afraid of covid-19 (adj OR:2.01), not believing in COVID-19 existence (adj OR:2.53), and not believing in vaccines (adj OR:4.25). Uncertainty about the COVID-19 vaccine is very prevalent among expectant mothers. The investigation accentuates the pressing need to administer COVID-19 vaccination to the general public, including expectant mothers who might be anxious about the vaccine.